Wide Distribution and Genetic Diversity of Babesia microti in Small Mammals from Yunnan Province, Southwestern China. - Zi-Hou Gao; Tao-Hua Huang; Bao-Gui Jiang; Na Jia; Zheng-Xiang Liu; Zong-Ti Shao; Rui-Ruo Jiang; Hong-Bo Liu; Ran Wei; Yu-Qiong Li; Hong-Wu Yao; Michael E von Fricken; et al. (PLOS Neglected Tropical Diseases, 2017)
BACKGROUND:Babesia, usually found in wild and domestic mammals worldwide, have recently been responsible for emerging malaria-like zoonosis in infected patients. Human B. microti infection has been identified in China, primarily in the Southwest along the Myanmar border but little direct surveillance of B. microti infection in rodents has been carried out here (Yunnan province). In this region, a diverse topographic range combined with tropical moisture sustains a high biodiversity of small mammals, which might play important role on Babesia transmission. METHODS:Small mammals were captured in 141 sample locations from 18 counties located Yunnan Province, and screened for B. microti-like parasites infection by a nested PCR to target 18S rRNA gene of Babesia, plus directly sequencing for positive samples. Univariate and multivariate forward stepwise logistic regression analysis was used to access the association between infections and some related risk factors. RESULTS:Infection with Babesia microti was confirmed in 2.4% (53/ 2204) of small mammals. Significant differences in prevalence rates of B. microti were observed based on variations in forest, agricultural, and residential landscapes. Furthermore, adult small mammals had higher prevalence rates than younger, pubertal mammals. The near full-length 18S rRNA gene revealed that there were two types of B. microti, Kobe and Otsu, which demonstrate the genetic diversity and regional distribution. CONCLUSIONS:There exists a wide distribution and genetic diversity of endemic B. microti in Southwestern China, warranting further investigations and monitoring of clinical disease in individuals presenting with Babesia like symptoms in these areas.